2020
DOI: 10.1038/s41598-020-63993-7
|View full text |Cite
|
Sign up to set email alerts
|

Decline of the boreal willow grouse (Lagopus lagopus) has been accelerated by more frequent snow-free springs

Abstract: Climate change has influenced a range of species across the globe. Yet, to state a noted decline in the abundance of a given species as a consequence of a specific environmental change, for instance, spatially explicit long-term data are a prerequisite. This study assessed the extent to which prolonged snow-free periods in autumn and spring have contributed to the decline of the willow grouse, the only forest grouse changing into a white winter plumage. Time-series data of willow grouse numbers from summer sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Willow ptarmigan are also sensitive to changes in climate which influence recruitment rates (Hannon & Martin, 2006;Martin & Wiebe, 2004;Slagsvold, 1975;Steen et al, 1988). In Europe, Melin et al (2020) demonstrated that population declines in Finland were more pronounced in years when the preceding April was snow-free, while Selås et al (2011) showed that chick production in Norway was related negatively to summer temperatures in the two previous years.…”
Section: Introductionmentioning
confidence: 99%
“…Willow ptarmigan are also sensitive to changes in climate which influence recruitment rates (Hannon & Martin, 2006;Martin & Wiebe, 2004;Slagsvold, 1975;Steen et al, 1988). In Europe, Melin et al (2020) demonstrated that population declines in Finland were more pronounced in years when the preceding April was snow-free, while Selås et al (2011) showed that chick production in Norway was related negatively to summer temperatures in the two previous years.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in winter climate concern also snow duration, which is now shorter than in the past, due to late snow arrival and early snow melt (Descamps et al, 2017; Liston & Hiemstra, 2011). Late onset of winter has been shown to hamper survival of color molting species including ptarmigan (Henden et al, 2020; Melin et al, 2020), likely due to camouflage mismatch resulting in elevated predation rates (Zimova et al, 2016). We used daily temperature data to calculate mean temperature (°C) in the core winter season (December t −1 –March t ) and onset of winter (Julian day).…”
Section: Methodsmentioning
confidence: 99%
“…Arctic species, such as the Arctic fox Vulpes lagopus, that exhibit colour polymorphisms and undergo seasonal colour moults, are interesting models for testing the relative importance of background matching as a camouflage tactic versus a role for thermoregulation in fur colour polymorphism. Species that undergo colour moult are of special relevance because long-term climate change has the potential to cause a mismatch in the seasonal camouflage that results in higher predation risk (Atmeh et al, 2018;Melin et al, 2020;Mills et al, 2013;Zimova et al, 2016). The Arctic fox has two colour morphs: white and blue.…”
Section: Introductionmentioning
confidence: 99%